Teaching Poetry in the Early Palaeologan School. Manuel Holobolos’ and John Pediasimos’ Commentaries on Theocritus’ Syrinx. - Caballero-Sánchez, Paula María (Cambridge University Press, 2022)
From the year 1265 on, the Palaiologan scholars-teachers Manuel/Maximos Holobolos (1243-1310/14) and John Pothos Pediasimos (ca. 1240-1310/14) devoted commentaries to the rediscovered Hellenistic pattern-poem Syrinx, attributed to Theocritus. This chapter explores their work on this text, focussing on their adaptation and rewriting of sources, and studies the scholarly context of the commentaries. Moreover, this contribution delves deeper into the influence of Holobolos' scholia on Pediasimos' commentary to the Syrinx.
https://www.cambridge.org/core/open-research/green-open-access-policy-for-books
Keywords: Imperio bizantino - Cultura; Poesía helenística; Byzantine studies; Bucolic poetry; History of Byzantine education and culture; Theocritus (classics); Hellenistic poetry; Byzantine scholarship and education; Palaiologan Byzantium